Belhar: 'n Spiritualiteit van resepsie in die plaaslike gemeente - Westhof, Leon E.; Nel, Malan (The Confession of Belhar: A spirituality of reception in the local church., 2014)
The General Synod of the Dutch Reformed Church took the following decision during October 2011: 'The General Synod decides to make the Confession of Belhar part of its confessional foundation, that is, in terms of its church ordinances, and commission the Moderamen to prepare the necessary processes regarding ecclesiastical law.' This article deals with the perception of, the reception of and resistance against Belhar as confession in a local congregation, Elardus Park. The research also describes how this obstructs the development of missional focus. The main contribution of this article is to argue that the ecumenical concept's full reception should be assessed within the broader framework of building up a missional local church where a spirituality of reception is fully developed in terms of a missional positioning in Africa.
free
Keywords: CHRISTIAN missions; CHRISTIAN spirituality; COUNCILS & synods; LOCAL councils of churches; NETHERLANDS Reformed Church